Метод усреднения в проблеме устойчивости движения твердого тела, подвешенного на струне - Кошляков, В.Н. (Український математичний журнал, 2007)
On the basis of the Bogolyubov – Mitropol’skii averaging method, we consider the stability of vertical rotation of a body suspended on a string.